Reevaluating surgery and re-irradiation for locally recurrent pediatric ependymoma—a multi-institutional study. Issue 1 (8th November 2021) - Mak, David Y; Laperriere, Normand; Ramaswamy, Vijay; Bouffet, Eric; Murray, Jeffrey C; McNall-Knapp, Rene Y; Bielamowicz, Kevin; Paulino, Arnold C; Zaky, Wafik; McGovern, Susan L; Okcu, M Fatih; Tabori, Uri; et al.
Abstract: Background: The goal of this study was to evaluate extent of surgical resection, and timing and volume of re-irradiation, on survival for children with locally recurrent ependymoma. Methods: Children with locally recurrent ependymoma treated with a second course of fractionated radiotherapy (RT2) from 6 North American cancer centers were reviewed. The index time was from the start of RT2 unless otherwise stated. Results: Thirty-five patients were included in the study. The median doses for first radiation (RT1) and RT2 were 55.8 and 54 Gy, respectively. Median follow-up time was 5.6 years. Median overall survival (OS) for all patients from RT2 was 65 months. Gross total resection (GTR) was performed in 46% and 66% of patients prior to RT1 and RT2, respectively. GTR prior to RT2 was independently associated with improved progression-free survival (PFS) for all patients (HR 0.41, P = 0.04), with an OS benefit (HR 0.26, P = 0.03) for infratentorial tumors. Median PFS was superior with craniospinal irradiation (CSI) RT2 (not reached) compared to focal RT2 (56.9 months; log-rank P = 0.03). All distant failures (except one) occurred after focal RT2. Local failures after focal RT2 were predominantly in patients with less than GTR pre-RT2. Conclusions: Patients with locally recurrent pediatric ependymoma should be considered for re-treatment with repeat maximal safe resection (ideally GTR) and CSI re-irradiation, with careful discussion of the potential side effects of these treatments.